Building Resilience through Sustainable Livelihoods and Technology: Climate Change and Food Security in West Africa - Omenka, Loveth C. Ode; Osabuohien, Evans S.; Matthew, Oluwatoyin A. (Universitas Medan Area, 2025)
Climate change has emerged as a critical driver of the ongoing food crisis, particularly in vulnerable regions such as West Africa. The study provided one of the few empirical investigations that examine how climate change and livelihood strategy interact to affect food security. Focusing on Nigeria and Senegal, the research compares households severely impacted by climate variability with those less affected, aiming to understand the role of Climate change and sustainable livelihood strategies in shaping food outcomes. The research was grounded on the Resilience theory, which explores household capacity to withstand environmental shocks, and the Sustainable Finance Theory, which highlights the importance of inclusive and stable economic systems. The study employed a mixed-methods approach. Quantitative data was sourced from the Living Standards Measurement Study–Integrated Surveys on Agriculture (LSMS-ISA) while qualitative insights were generated through an in-depth interview conducted in the largest soilless farm Lab in Africa. Findings revealed a significant impact of climate change and technology on food consumption. The results showed an interaction between climate change, livelihood, and food security in Nigeria and Senegal. The qualitative approach revealed a significant positive effect of techno-driven agriculture smart strategy on food consumption as well reduction of climate impact. The research recommended that climate-resilient, tech-driven agriculture should be embedded in national development frameworks, with a focus on scalability, local adaptation, and sustainability in climate-affected regions of West Africa, especially Nigeria and Senegal.